Atlas Ecological And Conservation Mapping: The Essence, Experience And Development Direction - Peresadko, V. A. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2014)
The experience of atlas regional ecological and conservation mapping has been analysed , its priority directions have been determined, the structure and content of the environmental conservation atlases of the region and the city for different purposes have been proposed for the children of primary school age, to high school as well as a medical and environmental reference atlas. The mathematical elements, display methods and design charts of the atlas have been determined